Prevalence of Endoscopic and Histological Lesions at Upper Endoscopy: A Cross-Sectional, Multicentre Study in Clinical Practice - Vincenzo De Francesco; Angelo Zullo; Arnaldo Amato; Irene Bergna; Emanuele Bendia; Giorgia Giorgini; Elisabetta Buscarini; Guido Manfredi; Sergio Cadoni; Renato Cannizzaro; Stefano Realdon; Mario Ciuffi; et al. (GE: Portuguese Journal of Gastroenterology, 2024)
Background/Aim: Prevalence of gastroduodenal endoscopic and histological lesions may modify over time due to different factors. We assessed both macroscopic and histological lesions currently detected at upper endoscopy performed in routine practice. Patients and Methods: Clinical, endoscopic, and histological data of consecutive adult patients referred for upper endoscopy in the 28 participating centres were analysed. Only patients who underwent the first endoscopic examination were considered. Prevalence of erosive/ulcerative lesions, cancers and extensive precancerous lesions in the stomach, and Helicobacter pylori infection was computed. Results: A total of 1,431 patients underwent endoscopy for gastro-oesophageal reflux symptoms (31.5%), dyspepsia (29.4%), or alarm symptoms (18.5%). Erosive oesophagitis or Barrett’s oesophagus was detected in 210 (14.7%) cases, peptic ulcer in 49 (3.4%), and a neoplastic lesion in 17 (1.2%). H. pylori was present in 201 (22.6%) cases, and extensive precancerous lesions on gastric mucosa in 46 (5.6%) patients. Gastric lesions were more prevalent in patients aged ≥50 years (26% vs. 18%; p = 0.001), and peptic ulcers were more frequently detected in patients with H. pylori (9.4% vs. 2.3%; p = 0.001) and in males (5.8% vs. 1.6%; p = 0.001), while neoplastic lesions in patients with alarm symptoms (3.8% vs. 0.6%; p = 0.001). Conclusions: The overall endoscopic lesions were more prevalent in patients aged ≥50 years, peptic ulcer and erosions were more frequent in H. pylori-infected patients, and extensive gastric precancerous lesions were present in less than 6% of cases.